Avaliação do uso dos subprodutos da dessulfurização semi-seca dos gases da combustão da termelétrica do Pecém como insumo para a construção civil - Santana, Raphael Arlego de Alcântara (2018)
Thermoelectric power plants contribute to reduce the strong national dependence on hydroelectric power dams, allowing the improvement of quality of energy distribution and the independence with respect to distance between generating source and urban centers. However, greenhouse gases that such plants release, as well as various solid wastes that may compromise underground and surface water sources, motivate several scientific research works, especially its application in concrete and mortar, which are two major materials used in civil construction. Previous works indicate that some of these solid wastes improve the mechanical properties and aspects of durability of these cementitious composites, being a possible alternative for a reduction of environmental liabilities and contributing to a more sustainable development. In Pecém I thermoelectric power plant (UTE Pecém I), contrarily to what is done in most of the plants in China and Europe, where there is a pre-collector of fly ash, allowing its separation from sulfurous residues, the flue gas desulphurization system (FGD) was installed before the ash collectors, similarly to United States plants, generating a residue called Spray Dryer Ash (SDA). The objective of this work is to evaluate, within civil construction, the use of SDA from UTE Pecém I. For this, the SDA of the plant in question was physically and chemically characterized and was classified according to ABNT NBR 10004: 2004. Then, the use of this waste as a mineral addition in concretes was evaluated by preparing mixtures with fck of 25 MPa with 0% (reference), 5%, 10% and 20% SDA relative to the cement mass, performing physical, chemical and mechanical properties characterization. Finally, the use of SDA was evaluated as a substitution of lime in external rendering mortars when making a reference mixture (0% SDA) and with substitutions of 33%, 67% and 100%, by volume. Fresh state tests, rheological analysis by squeeze-flow method, and hardened state tests were performed. The results showed that the SDA from UTE Pecém I is a non-hazardous non-inert waste (class II-A), which cannot be classified as class C pozzolan, among other reasons, because it has a high sulfur content. The mechanical strengths of the concrete mixtures were either not influenced or increased with increasing SDA content. The same occurred with the resistance of the mixtures of mortar with SDA. A highlight can be given to the mortar mixtures with 67% SDA, which presented superior resistance to the others, increased elasticity modulus and water absorption by capillarity, as well as a reduction of the entrained air content. It is concluded that the use of SDA as a mineral addition in concrete, according to the tests performed, has no technical restriction. In mortars it is possible to replace lime by SDA, but with caveats, since some of the properties tend to worsen with increase in the content of SDA, having to be controlled not to have deleterious effects when being used in civil construction.